Disiplin digital dan mediasi media oleh orang tua pada anak usia dini saat pandemi COVID-19 - Hardiyanti Pratiwi; Nor Izzatil Hasanah (Jurnal Psikologi Sosial, 2022)
Children use digital devices at an early age when the COVID-19 pandemic is increasing. Media mediation and digital discipline are needed so that increased access is accompanied by anticipation of negative content and strengthening the impression of positive content. This qualitative descriptive study aims to reveal the form of digital discipline and media mediation that parents apply to the use of digital devices by early childhood when implementing the work and study from home policy. The results showed that there were 3 types of disciplinary patterns applied by the participants in this study, namely: reducing the intensity and duration of access to digital devices, mitigating content, and combining the two. The discipline pattern is carried out with several strategies, namely: shifting activities, duration or situation restrictions, inhibition of access, and habituation. Meanwhile, the most frequently used media mediation by participants is the type of restrictive mediation. In addition, there are also those that combine various types of mediation, namely restrictive-co-viewing, technical-active, as well as restrictive-active.